Assessment of Bolbophorus damnificus prevalence and cercariae shedding in Planorbella trivolvis populations from catfish aquaculture ponds in Mississippi, USA. Issue 2 (13th December 2020) - Gunn, Mackenzie A.; Allen, Peter J.; Rosser, Thomas Graham; Wise, David J.; Khoo, Lester H.; Griffin, Matt J.
Abstract: Bolbophorus damnificus (Digenea: Bolbophoridae) causes significant losses in US catfish aquaculture. Little is known regarding the prevalence of infected snail hosts during outbreaks. To assess prevalence of snails observed shedding Bolbophorus spp. cercariae, as well as snails that were infected but not observed shedding cercariae, Planorbella trivolvis (n = 8, 159) were collected from 14 catfish production ponds with B. damnificus activity in Mississippi, USA. Individual snails were placed in 10 ml of filtered (20 μm) reservoir pond water and observed for 48 hr for cercariae release. Identification of B. damnificus or Bolbophorus sp. type II cercariae was confirmed by duplex PCR. Genomic DNA was isolated from ~100 non‐shedding snails from each pond and the PCR assay used to identify the presence of B. damnificus or Bolbophorus sp. type II infected snails. The prevalence of snails shedding B. damnificus ranged from 0.23 to 13.6%. Observation of cercariae shedding underestimated true B. damnificus and Bolbophorus sp. type II prevalence in 42.9 and 64.3% of sampled ponds, respectively. Prevalence of B. damnificus infected snails was typically <3%, indicating numbers of infected snails during outbreaks are low and mitigation efforts may be successful simply by reducing snail numbers and not require complete eradication.